2021
DOI: 10.1097/qai.0000000000002767
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: HIV Pre-exposure Prophylaxis Prescribing in an Urban Safety-Net Health System

Abstract: Introduction: Safety-net health systems are key settings for HIV pre-exposure prophylaxis (PrEP) implementation, but little evidence is available about the frequency of PrEP prescribing in safety-net settings. We assessed PrEP prescribing among people with indications for PrEP at an urban safety-net health system that serves a county designated as an Ending the HIV Epidemic priority jurisdiction. Methods:We identified adults (aged 18 years or older) who engaged in primary care between January 2015 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…Overall, approximately 10% of the patients who were included within our analysis received a prescription for PrEP. This prescription rate is slightly higher than studies within similar settings that have found PrEP prescription rates between 1% and 8% (17)(18)(19).…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Overall, approximately 10% of the patients who were included within our analysis received a prescription for PrEP. This prescription rate is slightly higher than studies within similar settings that have found PrEP prescription rates between 1% and 8% (17)(18)(19).…”
Section: Discussioncontrasting
confidence: 64%
“…However, this pattern has been reported in other studies. Indeed, older age has been correlated with increased odds of PrEP prescription (18,20), while Pitts et al found that White and Hispanic patients were more likely than Black patients to receive PrEP at an urban medical center (21). In a study that examined individuals who tested positive for an STI within the ED, Black patients were less likely to receive follow-up care (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Many studies find the cumulative incidence of PrEP prescriptions among those with indications for PrEP is less than 10%, including a study at an adolescent primary care center in the Deep South where the rate of prescription was 0%. 24,25 A 2015 study of providers found that those trained in internal medicine were 1.6 times more likely than infectious disease practitioners to have prescribed PrEP 26 ; among our study participants, none of those trained in internal medicine had prescribed PrEP compared to over 75% of those trained in pediatrics, obstetrics/gynecology, and family medicine. This contradictory finding may suggest that these providers who work frequently with AGYW may be more likely to have prescribed PrEP to a female client because they are already engaged in discussions about sexual health with this population.…”
Section: Discussionmentioning
confidence: 59%